2013
DOI: 10.1002/jctb.4133
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of P(3HBco4HB) copolymer with target‐specific 4HB molar fractions using combinations of carbon substrates

Abstract: BACKGROUND: The incorporation of 4HB units into P(3HB) improves the material application potential as the copolymer exhibits a wide range of physical properties ranging from crystalline plastic to elastic rubber depending on the copolymer composition. Thus, the prospects of synthesizing P(3HB-co-4HB) copolymer with various compositions of 4HB would increase its effectiveness as biomaterial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…A similar observation was also reported by Chanprateep et al (2008), which stated that 1,4-butanediol is one of the effective carbon precursors for the increase in the 4HB molar fraction as compared to γ-butyrolactone. Biosynthesis of P(3HB-co-4HB) involves the conversion of 1,4butanediol to 4-hydroxybutyryl-CoA, before being converted to 4-hydroxybutyrate, where only a portion of 4-hydroxybutyrate will undergo a complex pathway to form 3-hydroxybutyrate (Steinbüchel & Lütke-Eversloh, 2003;Iqbal & Amirul, 2014;Norhafini et al, 2017). Hence, this further confirmed that the utilization of the optimum amount of 1,4-butanediol could greatly promote the production of 4HB monomer in copolymer P(3HB-co-4HB).…”
Section: Effect Of Different Ratio Of Carbon Precursors On Bacterial ...supporting
confidence: 58%
“…A similar observation was also reported by Chanprateep et al (2008), which stated that 1,4-butanediol is one of the effective carbon precursors for the increase in the 4HB molar fraction as compared to γ-butyrolactone. Biosynthesis of P(3HB-co-4HB) involves the conversion of 1,4butanediol to 4-hydroxybutyryl-CoA, before being converted to 4-hydroxybutyrate, where only a portion of 4-hydroxybutyrate will undergo a complex pathway to form 3-hydroxybutyrate (Steinbüchel & Lütke-Eversloh, 2003;Iqbal & Amirul, 2014;Norhafini et al, 2017). Hence, this further confirmed that the utilization of the optimum amount of 1,4-butanediol could greatly promote the production of 4HB monomer in copolymer P(3HB-co-4HB).…”
Section: Effect Of Different Ratio Of Carbon Precursors On Bacterial ...supporting
confidence: 58%
“…When grown on any of the saturated FAs, C. necator IBP/SFU-1 produced cell concentrations comparable to those achieved on oleic acid, but polymer concentrations were lower ( Figure 2 ): 65.9 and 64.2% on lauric and myristic acids, respectively, and only 49% on palmitic acid. Similarly lower parameters were obtained on saturated FAs compared to oleic acid in studies of C. necator USMAHM13 [ 63 ] and C. necator USMAA2-4 [ 62 ]. The most likely explanation lies in the physiological and biochemical properties of each strain and its ability to metabolize a certain fatty acid.…”
Section: Resultsmentioning
confidence: 72%
“…Those values were comparable to the corresponding parameters reported for C. necator B-10646 [ 60 ] and other strains including Alcaligenes sp. NCIM N5085 [ 61 , 62 ] grown on the same FA. Polymer concentration synthesized by C. necator IBP/SFU-1 was higher but cell concentration was lower than those reported for C. necator USMAHM13 [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations